2020
DOI: 10.47291/efi.v66i2.870
|View full text |Cite
|
Sign up to set email alerts
|

The International Tourism Performance Amidst Several Intervention Events: More than 20 Years of Multi Input Intervention Analysis in Bali, Jakarta, and Kepulauan Riau Provinces

Abstract: As one of the priority sectors in economic development of Indonesia, tourism is expected to be the main key in accelerating economic and social growth, hence reducing poverty. The tourism performance, especially international tourism market, is highly prone to intervention events that can reduce the number of inbound tourists and produce a negative impact on economic development of the destination country. Therefore, anticipating and mitigating various intervention events is necessary to maintain the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Jurnal Dinamika Ekonomi Pembangunan https://ejournal.undip.ac.id/index.php/dinamika_pembangunan/index 28 include research on terrorism (Henderson 2003;Smyth et al, 2009) and climate-related natural disasters (Susanto et al, 2020). Research on the impact of multiple disaster events has been conducted by Rindrasih et al (2018) and Purwa and Atmanegara (2020). Rindrasih et al qualitatively analyzed fluctuations in foreign tourist arrivals related to terrorism, epidemics, tsunamis, and earthquakes.…”
Section: Jdepmentioning
confidence: 99%
See 1 more Smart Citation
“…Jurnal Dinamika Ekonomi Pembangunan https://ejournal.undip.ac.id/index.php/dinamika_pembangunan/index 28 include research on terrorism (Henderson 2003;Smyth et al, 2009) and climate-related natural disasters (Susanto et al, 2020). Research on the impact of multiple disaster events has been conducted by Rindrasih et al (2018) and Purwa and Atmanegara (2020). Rindrasih et al qualitatively analyzed fluctuations in foreign tourist arrivals related to terrorism, epidemics, tsunamis, and earthquakes.…”
Section: Jdepmentioning
confidence: 99%
“…This empirical finding is in line with Jónsdóttir's (2011) research, which explains that declines in visits to Iceland after the eruption of Mount Eyjafjallajökull lasted a relatively short time. Purwa and Atmanegara (2020), who specifically analyzed the flow of international tourists during the 2015 Mount Rinjani and 2017 Mount Agung eruptions, also revealed that a decline in visits only lasted a few months after the disaster.…”
Section: The Impact Of Natural Disastersmentioning
confidence: 99%
“…The Covid-19 pandemic has disrupted tourism performance as the main economic sector of Bali (Purwa & Atmanegara, 2020;Yuniti, Sasmita, Komara, Purba, & Pandawani, 2020;Atmojo & Fridayani, 2021;Handayani, Sylvina, & Lestari, 2021). Through the policy of social large-scale restrictions and travel restrictions for foreign tourists, the demand for tourism products has been drastically reduced, thus hampering economic activity The decline in the level of demand for tourism product are reflected by the lower contribution and economic contraction of the accommodation and food service activities Industry of Bali in 2020 as a macro tourism indicator, i.e.…”
Section: Introductionmentioning
confidence: 99%